Local Wisdom as a Pillar of Sustainable Environmental Policy: An Environmental Governance Perspective - Yusuf, Muhammad; Rafli, Muhammad; Hidayat, Rahmat Nur (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study examines the influence of local wisdom on environmental governance effectiveness within community contexts. Subjects and Methods: A quantitative approach was employed using survey data from 375 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. Results: The findings indicate that ritual practices, knowledge transmission, and customary sanctions have positive and significant effects on environmental governance effectiveness, both individually and simultaneously. Correlation and regression analyses reveal that these dimensions operate as an integrated system, reinforcing environmental awareness, compliance, and collective responsibility. The results also show that local wisdom enhances governance legitimacy and strengthens sustainable environmental behavior through cultural, cognitive, and social mechanisms. Conclusions: The study concludes that local wisdom plays a crucial role in improving environmental governance effectiveness. Integrating cultural values into environmental policies provides a contextually relevant and sustainable approach to achieving long-term environmental management outcomes.